Research of single sign-on in grid - MENG Fan-rong1; XIE Hong-xia1; WANG Ru-chuan2; XIA Shi-xiong1 (Tongxin xuebao)
Grid was a kind of new-type network computing platform following World Wide Web;An infrastructure of sharing different resources including webpage in an all-round way was offered.In order to complete one task,many re-sources were often needed the participants to assort with,so single sign-on to simplify users’ operations was needed.The disadvantages of single sign-on were analyzed,and a solution based on SAML was proposed,the test and the perform-ance evaluation to it had been carried on.